The interface of SiO2/ZnS films studied by high resolution X-ray photoluminescence. Issue 1 (January 2018) - Acharya, Shinjita; Trejo, Orlando; Dadlani, Anup; Torgersen, Jan; Berto, Filippo; Prinz, Fritz
HIGHLIGHTS: A clear shift of the S 2p peak with the number of deposition cycles showing that S is present in many different environments at the interface The confirmation of the surface confinement of this species as revealed by the XPS measurements at different angles. In a depth profile, the shift of the S 2p to higher energy is correlated to the rise of the Si 2p peak giving additional evidence that SO4 2- does not develop upon the exposure of the sample to air but is in fact a species for ZnS nucleation. ABSTRACT: Sharp interfaces in optoelectronic devices are key for proper band alignment. Despite its benefits as buffer layer, ZnS deposited via atomic layer deposition (ALD) renders intermixed interfaces to its substrate, which can be detrimental for device performance. Here, we are attempting to elucidate the chemical species deriving from this metal-oxide to metal-sulfide transition studying ultrathin film ZnS on SiO2 using high resolution X-ray photoluminescence spectroscopy (XPS). Regarding the S 2p spectra after a deposition of only three cycles of ZnS, we discover the many different chemical species in which S is present. These include intermediate oxides such as SO4 2- . These species become more obvious as we tilt the sample in the XPS chamber to shallower angles. Comparing the Si 2p and S 2p high resolution peaks in the depth profile, one can clearly uncover the confinement of SO4 2- to the interface of the underlying substrate. This may indicate that SiO2 /ZnS interfaces contain interfacial sulphates that likely alter the electronic configuration of this interface.